2015
DOI: 10.1371/journal.pone.0123061
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analyses of Serratia marcescens FS14 Reveals Its High Antagonistic Potential

Abstract: S. marcescens FS14 was isolated from an Atractylodes macrocephala Koidz plant that was infected by Fusarium oxysporum and showed symptoms of root rot. With the completion of the genome sequence of FS14, the first comprehensive comparative-genomic analysis of the Serratia genus was performed. Pan-genome and COG analyses showed that the majority of the conserved core genes are involved in basic cellular functions, while genomic factors such as prophages contribute considerably to genome diversity. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 73 publications
5
26
0
Order By: Relevance
“…25 In agreement with the chemical structure, multilocus sequence analysis (MLSA) performed with the amino acid sequences of eight protein homologs encoded on undecylprodigiosin red and prodigiosin pig clusters, and involved in biosynthesis the MBC precursor (RedWIOMNYV/ PigAFGHIKM) and precursors condensation (RedH/PigC), separated gram-negative prodiginiosin producers from actinobacteria undecylprodigiosin-related prodiginine producers in two main clades. 26 Therefore, the enzymology codified on the detected contig NODE_44 is in agreement with that expected for the biosynthesis of nonylprodigiosin and derivatives.…”
Section: Genome Miningsupporting
confidence: 76%
“…25 In agreement with the chemical structure, multilocus sequence analysis (MLSA) performed with the amino acid sequences of eight protein homologs encoded on undecylprodigiosin red and prodigiosin pig clusters, and involved in biosynthesis the MBC precursor (RedWIOMNYV/ PigAFGHIKM) and precursors condensation (RedH/PigC), separated gram-negative prodiginiosin producers from actinobacteria undecylprodigiosin-related prodiginine producers in two main clades. 26 Therefore, the enzymology codified on the detected contig NODE_44 is in agreement with that expected for the biosynthesis of nonylprodigiosin and derivatives.…”
Section: Genome Miningsupporting
confidence: 76%
“…Micrococcus luteus and Ralstonia solanacearum were used as the indicator microorganisms to investigate the antagonistic activities of YD25 T against bacterial pathogens. The biofilm and planktonic culture were used to assay antibacterial competition as described previously [48]. Samples containing only YD25 T or bacterial pathogens were set up as controls.…”
Section: Methodsmentioning
confidence: 99%
“…We have studied the involvement of other secretion machineries in the fungal invasion by S. marcescens D1. Comparative genome analysis of Serratia marcescens revealed that the type VI secretion system is abundant among various strains [32], which is used to target other bacterial competitors [33]. The T6SS effectors to antagonize fungal pathogens has also been reported in S. marcescens [51].…”
Section: Discussionmentioning
confidence: 99%